Antioxidant status & lipid peroxidation in patients with rheumatoid arthritis - Karatas, F; Ozates, I; Canatan, H; Halifeoglu, I; Karatepe, M; Colak, R (Scientific Scholar Llc, 2003)
Background & objectives: Rheumatoid arthritis (RA) is a debilitating, chronic multisystem disease with an unknown etiology. Recent findings indicate that increased oxidative stress and/or defective antioxidant status contribute to the etiology of RA. The present study was undertaken to examine the oxidant and antioxidant systems in patients with RA and healthy controls. Methods: Twenty two patients with RA and 20 healthy volunteers were included in the study. Levels of malondialdehyde (MDA) and antioxidant vitamins (A, E, C) in serum samples were determined by high performance liquid chromatography (HPLC). Spectrophotometric methods were used to determine activity levels of antioxidant enzymes, superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px), in erythrocytes. Results: MDA levels in patients with RA were found to be significantly (P < 0.005) higher than controls whereas levels of vitamins A, E, C and activities of GSH-Px, SOD were lower in the patients compared to controls (P < 0.005 for SOD and antioxidant vitamins; P < 0.05 for GSH-Px). Interpretation & conclusion: There was an increased oxidative stress and a low antioxidant status in patients with RA. These changes are probably due to efforts for reducing lipid peroxidation and hence to lower tissue damage.
Keywords: glutathione peroxidase; malondialdehyde; oxidative stress; rheumatoid arthritis; superoxide dismutase